A no-reference method of geometric content quality analysis of 3D models generated from laser scanning point clouds for hBIM. - Fryskowska, Anna; Stachelek, Julita (Journal of Cultural Heritage, 2018)
Abstract Laser scanning technology and modern photogrammetry have become very popular techniques in cultural heritage data acquisition. In the majority of architectural applications of these methods for historic buildings, relatively less attention is paid to the quality of the visualisation. However, when it is necessary to reconstruct the structure, materials, or form of a given heritage building or object, geometrical quality is key in the process of rebuilding or reconstruction. This paper proposes an assessment of geometrical content of 3D models for Heritage Building Information Modelling (hBIM) without reference measurements and independently of the data acquiring method or point cloud resolution. The point cloud analysed in this paper was obtained by terrestrial laser scanning (TLS); however, the analysis could be applied to point clouds of other origins (e.g. ALS, UAV imagery). The inner characteristics of measurement methods are not considered, with the focus on answering the following questions: How much will the point cloud allow us to see? and Is too much data always a good thing? The quality can simply be defined as the suitability of a specific dataset for a specific purpose. It is very important to clarify in advance for what kind of outcome a dataset might be or not be suitable, and which are the results expected.